Наукове обґрунтування та розроблення технологій сушеної харчової продукції та харчових продуктів з її використанням - Нєміріч, Олександра Володимирівна (My University, 2019)
Дисертація на здобуття наукового ступеня доктора технічних наук за спеціальністю 05.18.16 – технологія харчової продукції. – Національний університет харчових технологій, Київ, 2019. Дисертацію присвячено розробленню науково обґрунтованих технологій харчових продуктів з використанням сушеної харчової продукції (СХП) шляхом формування та реалізації її функціонально-технологічного потенціалу за допомогою сушіння зі змішаним теплопідведенням (ЗТП-сушіння). Теоретично та експериментально обґрунтовано наукову концепцію роботи, яка полягає в тому, що в ході сушіння відбувається формування функціонально-технологічного потенціалу СХП (здатність до диспергування, гідратаційна, жироутримуюча, емульгуюча здатності, число аромату, стійкість при зберіганні), які дозволяють розробити, удосконалити, інтенсифікувати і адаптувати технології харчових продуктів з її використанням для різних умов виробництва з отриманням гарантованої доданої вартості. Dissertation for the degree of doctor of technical sciences in the specialty 05.18.16 – Technology of food products. – National University of Food Technologies, Kyiv, 2019. The dissertation is devoted to development of scientifically based technologies of food stuff with use of dried food products by formation and realization of its functional and technological potential by means of drying with the mixed heat supply (MHS-drying). Theoretically and experimentally substantiated the scientific concept of the work, which lies in the fact that during the drying process the functional and technological potential of dried food products (DFP) is formed – dispersive, hydration, emulsifying abilities, ability to hold fat, aroma number, storage stability, – which is caused by physicochemical and colloid properties, is a basis of improvement and development of innovative high-tech food technologies, expansion of the range of foodstuff, allows to adapt technologies for various conditions of production (the enterprise of the food industry, restaurant establishments, including bistro and also living and special working conditions) with obtaining added value. The choice of raw materials of plant and animal origin, operation and the parameters of its preliminary heat treatment are reasonable – steam boiling of meat raw materials, scaldings of vegetable raw materials, chopping dried rosehips on fraction with particle size (30...60)  10–6 m mixing with blood of cattle.
Keywords: кафедра технології ресторанної і аюрведичної продукції; наукоємні інноваційні технології; сушена харчова продукція; сушіння зі змішаним теплопідведенням; функціонально-технологічні властивості; технологічний потік; харчові продукти; high-tech innovative technologies; dried food products; drying with the mixed heat supply; functional and technological properties; process flow; foodstuff